1993
DOI: 10.1128/aem.59.12.4335-4337.1993
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Packaging and Processing Conditions on the Decontamination of Laboratory Biomedical Waste by Steam Sterilization

Abstract: The conditions for optimal steam decontamination of polypropylene bags half loaded with laboratory biomedical waste were studied (276 bags were processed). Controls were single-closed bags without water added or incisions made in the top, standing freely in an autoclave set at 121°C. The average time required to reach 121°C at the load center was 46 min for controls. A significant increase in this time occurred following addition of water to bags without incisions (60 min), with double bagging (60 min), or whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that air trapped in a load can create insulating pockets that interfere with thermal transfer and result in longer cycle times needed to reach sterilizing temperatures. 7,8 Once 2 extra prevacuum pulses were added to the decontamination cycle, all of the BIs passed. Adding extra pulses has been previously shown to reduce the equilibration time needed for thermocouples placed within dry goods loads 9 and, in this study, could have better allowed the steam to reach any air pockets between the ferret carcasses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that air trapped in a load can create insulating pockets that interfere with thermal transfer and result in longer cycle times needed to reach sterilizing temperatures. 7,8 Once 2 extra prevacuum pulses were added to the decontamination cycle, all of the BIs passed. Adding extra pulses has been previously shown to reduce the equilibration time needed for thermocouples placed within dry goods loads 9 and, in this study, could have better allowed the steam to reach any air pockets between the ferret carcasses.…”
Section: Discussionmentioning
confidence: 99%